2011
DOI: 10.1007/s10447-011-9113-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Optimism as Predictors of Life Satisfaction of College Students

Abstract: The purpose of this study was to investigate the predictive value of optimism, perceived support from family and perceived support from faculty in determining life satisfaction of college students in Turkey. One hundred and thirty three students completed the Satisfaction with Life Scale (Diener et al., 1985) and provided demographic information about themselves. Independent samples t-test, correlation, and multiple regression analyses were performed for data analysis. Significant relationships were found amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 40 publications
3
29
1
10
Order By: Relevance
“…Our findings indicate that social support had a main effect on both the adjustment and academic achievement of all college students. This finding is consistent with research on students without disabilities (Mattanah, Ayers, Brand, Brooks, Quimby, & McNary, 2010;Wilks & Spivey, 2010;Yalcin, 2011), but it extends previous findings by showing that social support is a salient predictor of adjustment and achievement among college students with LD. Thus, social support received from family, friends, or teachers who believe in the young person's ability to succeed may act as a protective factor for students with LD and, therefore, is more significant in this population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings indicate that social support had a main effect on both the adjustment and academic achievement of all college students. This finding is consistent with research on students without disabilities (Mattanah, Ayers, Brand, Brooks, Quimby, & McNary, 2010;Wilks & Spivey, 2010;Yalcin, 2011), but it extends previous findings by showing that social support is a salient predictor of adjustment and achievement among college students with LD. Thus, social support received from family, friends, or teachers who believe in the young person's ability to succeed may act as a protective factor for students with LD and, therefore, is more significant in this population.…”
Section: Discussionsupporting
confidence: 91%
“…A large body of research has found social support to be positively correlated with psychological outcomes, such as greater life satisfaction, as well as lower levels of depression, anxiety, and loneliness (Bakker et al, 2005;Karatepe & Olugbade, 2009;Yalcin, 2011). Furthermore, social support from parents, peers, and others has been identified as an important protective factor that can enhance positive developmental outcomes among college students in the presence of known risks (Sarason & Sarason, 2009;Wilks & Spivey 2010).…”
Section: Perceived Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Several positive psychology studies among student populations have also shown that optimism is strongly associated with students' life satisfaction (e.g., Tuckwiller & Dardick, 2018;Yalçin, 2011). In this regard, in their study among college students Yu and Luo (2018) found that dispositional optimism positively correlated with well-being.…”
Section: Introductionmentioning
confidence: 87%
“…(Aydın ve Tezer, 1991;Haugen, Ommundsen, ve Lund, 2004;Gustavsson-Lilius, Julkunen ve Hietanen, 2006;Yalçın, 2011 Aile, insanın kişilik özelliklerinin belirleyicisi ve tamamlayıcısıdır. Bir insan hakkında kesin bir yargıya ulaşabilmek için onun yetiştiği aile içerisindeki rolü ile ilgili bilgiye ihtiyaç duyulmaktadır (Cüceloğlu, 1992;Yörükhan, 2011).…”
Section: Introductionunclassified